Transophthalmic Artery Embolization of Anterior Skull Base Meningiomas: Technical Case Series - Essibayi, Muhammed Amir; Baker, Amanda; Ryvlin, Jessica; Pecorari, Isabella; Fortunel, Addison; Hamad, Mousa; Khatri, Deepak; Crisman, Celina; Eskandar, Emad N.; Haranhalli, Neil; Agarwal, Vijay; Altschul, David J. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Preoperative embolization of anterior skull base meningiomas can facilitate surgical resection by reducing tumor vascularity. However, transophthalmic artery embolization carries risks of visual complications. This study aimed to evaluate the safety and efficacy of this technique by using modern endovascular tools.MATERIALS AND METHODS: This retrospective study included patients with anterior skull base meningiomas who underwent preoperative transophthalmic artery embolization followed by surgical resection between January 2022 and April 2024. Patient demographics, tumor characteristics, embolization details, surgical outcomes, and complications were analyzed.RESULTS: Seven patients (median age 57 years; 6 men) underwent embolization for tumors located primarily at the planum sphenoidale (58%). Unilateral embolization was performed in most cases, with 1 bilateral transophthalmic approach. Commonly embolized branches included the anterior and posterior ethmoidal arteries. Polyvinyl alcohol particles were the primary embolic agent (71%). Angiographic devascularization was achieved in all cases without complications. Gross total resection was achieved in 71%, with a median blood loss of 427 mL. At a 9-month follow-up, the median mRS score was 1.CONCLUSIONS: With careful patient selection, advanced microcatheter technology, and meticulous technique, preoperative transophthalmic artery embolization can be safely performed to facilitate resection of anterior skull base meningiomas. These results suggest it is a viable option for well-selected patients at experienced centers, though larger prospective studies are needed.IQRinterquartile rangePVApolyvinyl alcoholTOAEtransophthalmic artery embolization